Influence of the Nernst diffusion layer thickness on surface concentration in a model electrochemical process with a preceding chemical reaction - O. I. Gichan (Хімія, фізика та технологія поверхні, 2023)
The influence of the Nernst diffusion layer thickness on the surface concentrations of electroactive and electroinactive species in a model electrochemical process with a preceding homogeneous first-order chemical reaction under application of a small amplitude alternating current has been investigated. A case of equal diffusion coefficients of species taking part in the preceding chemical reaction in a thin layer attached to a planar electrode is considered. It has been shown that, at low frequencies of an applied alternating current, the surface concentrations of electroactive and electroinactive species increase with increasing the Nernst diffusion layer thickness. At high frequencies, the surface concentrations of both species do not depend on this parameter. However, there is a range of frequencies where the surface concentrations of species can decrease with increasing the Nernst diffusion layer thickness. This range of frequencies can be influenced by a value of the Nernst diffusion layer thickness, the rate constants of chemical reaction, and the diffusion coefficient of species. There exists a phase shift between an alternating current and the surface concentrations of electroactive and electroinactive species that change under application of this current. It is a function of the Nernst diffusion layer thickness, the oscillation diffusion layer thickness, and the reaction layer thickness. In the case of electroactive species, the phase angle can take only a positive value. At low frequencies, it tends to ?/2, whereas at high frequencies it decreases to ?/4. For the case of electroinactive species, the phase angle can be positive, negative, and equal to zero depending on the value of the Nernst diffusion layer thickness, the rate constants of chemical reaction, and the diffusion coefficient of species. It approaches –?/2 at low frequencies, and at high frequencies it tends to ?/4. The both phase angles can have the maxima and the minima. Their values are strongly dependent on the Nernst diffusion layer thickness, the diffusion coefficient of species, the rate constants of chemical reaction.